Strategi Pengembangan UMKM Games in Your Area melalui Optimalisasi Digital Marketing - Shevia, Shevia; Christiarini, Renny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2023)
In the era of the fourth industrial revolution in Indonesia, it is crucial for Micro, Small, and Medium Enterprises (MSMEs) to continuously update themselves to survive in the midst of intense competition. This study explores a development strategy for the MSME